G.K. Hall encyclopedia of modern technology - Blackburn, David; Holister, Geoffrey (G.K. Hall & Co., 1987)
Color illustrations and diagrams explain the major principles underlying modern technology including particle accelerators, laser discs, turbine engines, and guided missile control.